Literature Review : Company Value in Providing Trust to Customer Loyalty - Suryawan, Ryan Firdiansyah; Soehaditama, Josua Panatap; Prihanto, Y. Johny Natu; Muliyati, Muliyati; Sjarifudin, Didin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This paper aims to illustrate the crucial role of trust in building and maintaining customer loyalty in a business context. The paper also highlights unique challenges in the Umrah travel industry in Indonesia, with an emphasis on how companies address potential mistrust. Qualitative by search comes from the literature related to the variables in this paper by looking for findings and providing reinforcement, additional contributions from all results in the literature. The time span of literature in the past eight years. Companies can cultivate a community of loyal customers who invest in a relationship with a brand they trust implicitly, trust emerges as a lived value that fuels an enduring and meaningful relationship between the company and its customers. Companies can strengthen their commitment to building trust, thereby fostering enduring customer loyalty and creating a positive and sustainable brand image in the marketplace.